Two-stage three-channel Kondo physics for an FePc molecule on the Au(1 1 1) surface. (28th August 2018) - Fernández, J; Roura-Bas, P; Camjayi, A; Aligia, A A
Abstract: We study an impurity Anderson model to describe an iron phthalocyanine (FePc) molecule on Au(1 1 1), motivated by previous results of scanning tunneling spectroscopy (STS) and theoretical studies. The model hybridizes a spin doublet consisting in one hole at the orbital of iron and two degenerate doublets corresponding to one hole either in the 3 d xz or in the 3 d yz orbital (called π orbitals) with two degenerate Hund-rule triplets with one hole in the 3 d z orbital and another one in a π orbital. We solve the model using a slave-boson mean-field approximation (SBMFA). For reasonable parameters we can describe very well the observed STS spectrum between sample bias −60 mV to 20 mV. For these parameters the Kondo effect takes place in two stages, with different energy scales corresponding to the Kondo temperatures related with the hopping of the z 2 and π orbitals respectively. There is a strong interference between the different channels and the Kondo temperatures, particularly the lowest one is strongly reduced compared with the value in the absence of the competing channel.